2019
DOI: 10.1063/1.5121379
|View full text |Cite
|
Sign up to set email alerts
|

Ge doped GaN and Al0.5Ga0.5N-based tunnel junctions on top of visible and UV light emitting diodes

Abstract: The use of tunnel junctions (TJs) is a potential solution in blue LEDs to poor p-contacts, replacing it by another n-contact. TJs are even more advantageous for UV emitting structures, which suffer from the considerably low injection efficiency in high Al concentration UV LEDs. In this work we report our work on Ge n-doped GaN and AlGaN TJs grown on top of blue and UV LEDs, respectively, by a hybrid growth. We have achieved state of the art mobility (67cm 2 /V.s) and resistivity (1.7x10 -4 Ω.cm) at a free elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
(46 reference statements)
2
35
0
Order By: Relevance
“…Indeed, considering average values for the different efficiencies in our devices, i.e., with an IQE of 20%, an EE of 8% (estimated from the extraction cone at the sapphire/air interface) and an EQE of 0.05-0.1%, it is then possible to estimate the IE which is in the range of 3 to 6% only. Inefficient hole injection due to low hole concentration and mobility in high Al concentration Al x Ga 1−x N layers leads to electron leakage and overflow out of the active region and will require different layer designs such as tunnel junctions which have been shown as an attractive solution to improve the IE and avoid the use of an absorbing p-type GaN contact [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, considering average values for the different efficiencies in our devices, i.e., with an IQE of 20%, an EE of 8% (estimated from the extraction cone at the sapphire/air interface) and an EQE of 0.05-0.1%, it is then possible to estimate the IE which is in the range of 3 to 6% only. Inefficient hole injection due to low hole concentration and mobility in high Al concentration Al x Ga 1−x N layers leads to electron leakage and overflow out of the active region and will require different layer designs such as tunnel junctions which have been shown as an attractive solution to improve the IE and avoid the use of an absorbing p-type GaN contact [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years there has been a renewed interest in highly doped n -GaN layers produced by metal-organic vapor-phase epitaxy (MOVPE). Such layers are very important for the optimization of the operative voltage of GaN-based electronic devices, especially those with tunnel junctions [ 1 ], as well as for controlling the layers’ refractive index thanks to the plasmonic effect [ 2 ]. For all these applications, it is desirable to reach higher doping levels than those achievable with silicon as a donor impurity.…”
Section: Introductionmentioning
confidence: 99%
“…Even if Mg can be activated by annealing after the p-layer growth [20][21], it is at least partially re-passivated during the subsequent growth of the n-layer on top of the p-layer to fabricate the TJ. A new approach consists of growing the n + -side of the TJ by ammonia-based molecular-beam epitaxy (NH3-MBE) directly on an LED device synthesized by metal organic chemical vapor deposition (MOCVD) [7,22].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study is to correlate the chemical, structural and electrical properties of a Mg/Gedoped TJ grown on top of a InxGa1-xN/GaN-based LED. It has already been demonstrated that this architecture leads to an enhancement of the LED emission [22]. However, the in-depth understanding of the tunneling mechanisms requires an assessment of the distribution of dopants at the p/n interface, i.e.…”
Section: Introductionmentioning
confidence: 99%